Spatial Changes of Ocean Circulation Along the Coast of Gulf of Thailand Using Tide Gauge Measurements - Kutubuddin Ansari; José Francisco de Oliveira‐Júnior; Punyawi Jamjareegulgarn (IEEE Access, 2022)
The study presents linear and nonlinear (smoothing spline) modeling of sea-level measurements on the basis of 50-year (1971-2020 A.D.) permanent service for mean sea-level (PSMSL) tide gauge data at the coastal area of the Gulf of Thailand. These tide gauge measurements are compared with the ORAS5 data extracted from the latest ECMWF atmospheric reanalysis-ERA5. The comparative analyses showed that both kinds of data are correlated with a correlation coefficient of more than 0.94. Moreover, to examine the performance and the complexity of tide gauge measurements at each site, the multitaper spectral analysis is carried out and the spectral estimates are also estimated. Our spectral analyses showed that the sea-level measurements at each site have different levels of fluctuation because of individual local influence. The proposed multitaper spectral analysis can be considered as an appropriate method for tide gauge analysis and can be applied to attain the fluctuation of sea-level at the global level.
Keywords: Oceanographic and Atmospheric Processes; Geophysics and Gravity Measurements; Ocean Waves and Remote Sensing